2018
DOI: 10.3390/agriengineering1010003
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-Up Biodiesel Production from Meat Processing Dissolved Air Flotation Sludge: A Simulation Study

Abstract: For the first time, a steady state computational simulation for the production of biodiesel from meat processing dissolved air flotation sludge via an integrated process of in-situ hydrolysis and esterification technologies has been investigated. Important thermophysical properties of the intrinsic lipids of dissolved air flotation sludge were estimated using chemical constituent fragment methods. The environmental performance and the economic performance of the biodiesel production process were assessed via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 49 publications
(92 reference statements)
0
16
0
Order By: Relevance
“…To reflect possible effects of inflation, the annualised capital cost in the present year of 2019 (C 2019 ) was estimated from the calculated annualised capital cost for the reference year of i (C i ), using the chemical engineering plant cost (CEPCI) index as follows [28];…”
Section: Annual Operating and Annualised Capital Cost Per Unit Volumementioning
confidence: 99%
See 3 more Smart Citations
“…To reflect possible effects of inflation, the annualised capital cost in the present year of 2019 (C 2019 ) was estimated from the calculated annualised capital cost for the reference year of i (C i ), using the chemical engineering plant cost (CEPCI) index as follows [28];…”
Section: Annual Operating and Annualised Capital Cost Per Unit Volumementioning
confidence: 99%
“…The annualised capital cost in US $ for year i, for biogas desulphurisation system, with reference capacity, vref in m 3 , and denoted by C i , vref was subsequently estimated as follows [28];…”
Section: Annual Operating and Annualised Capital Cost Per Unit Volumementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that meat processing dissolved air flotation (DAF) sludge can serve as a cheap and sustainable biodiesel feedstock via an integrated two-step in-situ hydrolysis and esterification pathway [2]. Crucially however, the utilization of meat processing DAF sludge as a biodiesel feedstock will result in the generation of significant masses of wet hydrolyzed DAF sludge (WHDS) after the biodiesel production process [3,4]. This WHDS residue was identified as constituting a secondary waste stream that must be efficiently utilized to prevent possible secondary pollution issues.…”
Section: Introductionmentioning
confidence: 99%